PENGARUH BAURAN PROMOSI DAN CITRA MEREK TERHADAP MINAT KONSUMENPADA ALPHA HOTEL PEKANBARU - Manurung, Ciin Opelti; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of Promotion And Brand Image Toward Consumer Interest in Alpha Hotel Pekanbaru. Where two independent variables and one dependent variable are promotional mix and brand image as independent variable and consumer interest act as dependent variable. The population in this research is Alpha Hotel Pekanbaru visitors with sampling amounted to 100 people which calculated by using Slovin formula. The sampling technique was done by purposive sampling method. The research data collected in the form of primary data by using kusioner as research instrument, data analysis used is by using linear regression analysis along with the help of SPSS program. From the results of tests conducted show that the promotion mix and brand image have a positive and significant impact on consumer interest. where the value of coefficient of determination (R2) shows that the variable of promotion mix and brand image contributes to consumer interest variable of 34.5 while the rest of 65,5 is influenced by other variable not included in this research.Keywords: marketing mix, promotion mix, brand image, consumer interest